Profils de valeurs de travail et centralité du travail chez des élèves du secondaire - Mottais, Évelyne; Busque-Carrier, Mathieu; Bourdon, Sylvain (Canadian Journal of Education/Revue canadienne de l’éducation, 2025)
The four-factor model of work values (MQF-VT) was developed and empirically validated to incorporate the main work values identified in the scientific literature. The aim of this study is to verify the presence of work value profiles based on the MQF-VT from a sample of Quebec high school students (n = 3,083). It also aims to describe the association between work value profiles and work centrality (i.e., the importance a person places on work in his or her life), as well as sociodemographic characteristics. The data was collected via an online survey. An exploratory structural equation modelling analysis was used to estimate the factor structure of the MQF-VT. A latent profile analysis yielded five profiles generally similar to those identified in a previous study. A comparison analysis of these profiles indicates that the level of work centrality varies according to profile membership. The originality of this article is to support the validity of the theoretical model and the resulting profile solution, which contributes to its generalization. In practice, the results show the importance of guidance practitioners making use of work values in their intervention with high school students.